2016
DOI: 10.1037/xge0000146
|View full text |Cite
|
Sign up to set email alerts
|

The genetic and environmental etiologies of the relations between cognitive skills and components of reading ability.

Abstract: While previous research has shown cognitive skills to be important predictors of reading ability in children, the respective roles for genetic and environmental influences on these relations is an open question. The present study explored the genetic and environmental etiologies underlying the relations between selected executive functions and cognitive abilities (working memory, inhibition, processing speed, and naming speed) with three components of reading ability (word reading, reading comprehension, and l… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
16
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
8
1
1

Relationship

1
9

Authors

Journals

citations
Cited by 22 publications
(17 citation statements)
references
References 45 publications
(83 reference statements)
1
16
0
Order By: Relevance
“…The current study did not address the etiology of the sex difference in dyslexia, but previous work in this sample indicates genetic covariation between reading skill and the cognitive correlates studied here (Christopher et al, 2016;Willcutt et al, 2010).…”
Section: Discussionmentioning
confidence: 93%
“…The current study did not address the etiology of the sex difference in dyslexia, but previous work in this sample indicates genetic covariation between reading skill and the cognitive correlates studied here (Christopher et al, 2016;Willcutt et al, 2010).…”
Section: Discussionmentioning
confidence: 93%
“…This deficit may subsequently distort proper development of cortical representations that are essential for reading acquisition (Hari and Renvall, 2001). Moreover, genetic studies have shown that variation in reading performance is explained by specific genes and by a set of genes in common with pWM (Christopher et al, 2016;van Leeuwen et al, 2009), suggesting a common underlying genetic factor. It is therefore plausible to hypothesize a specific detrimental effect of SRDcandidate genes upon the phonological loop (Baddeley, 2003), which has been shown to be distinctly impaired in subjects with SRD compared to normal readers (Swanson et al, 2009), rather than upon the sequence processing in general.…”
Section: Discussionmentioning
confidence: 99%
“…However, the "phenotype" educational attainment has been operationally defined in many different ways, such as years of education (Okbay et al, 2016), highest degree completed (Belsky et al, 2016), and score on a U.K. nationwide examination (Rimfeld et al, 2015;Shakeshaft et al, 2013). It is also possible to study the link between genetics and certain components of education attainment such as mathematics (Chen et al, 2017;Wang et al, 2014) or reading (Christopher et al, 2016;Davis et al, 2014;Gialluisi, Guadalupe, Francks, & Fisher, 2016). It is unclear whether these different measurements of educational attainment are all tapping into the same phenotype, or instead measuring distinct components of behavior.…”
Section: Phenotype Measurementsmentioning
confidence: 99%